Fatal pediatric injuries in Iceland 1980-2010: A population-based study - Steinunn Anna Eiríksdóttir 1981- (2016)
Background: Injury has been one of the leading causes of pediatric fatalities in the world. Previous studies on fatal pediatric injuries have shown that injury incidence rates have been declining over the years. Boys have appeared to be more likely to be injured than girls, head injuries are the most common cause and age group, socioeconomic status and accident location may all have impact. Combining extensive official databases by personal social security numbers allowed for a wide exploration of variables on studying fatal pediatric injuries in Iceland. The aim was to investigate the epidemiology of fatal pediatric injuries among Icelandic children, from birth to 17 years old, from 1980 to 2010. Method: This was a population based descriptive register study. Data, obtained from the Causes of Death Registry at the Directorate of Health and Statistics Iceland, included information on all fatal injuries among Icelandic children, 0 to 17 years old, from 1980 to 2010; type of injury, age, sex, accident location (rural/urban) and number of adults and siblings living with the child. Proportions by background factors were calculated. Rate per 100.000 person per year were calculated where possible using Poisson regression model. Trends were analyzed using chi-squared test for the rates and proportions and likelihood ratio test for rate per person year. Results: During the study period 263 children died as a cause of unintentional injury. The most common causes of death were head injuries (41,1%), drowning (17,5%), multiple injuries (14,1%), injuries to the chest (7,6%) and suffocation (6,8%). Boys constituted 69,2% of the fatalities. Most fatalities occurred in the age group 15-17 years (41,1%). More fatalities occurred in rural areas (58,5%) and the majority of individuals studied lived with two adults (77,2%) and two siblings or less (89,4%) at the time of death. The incidence decreased during the study period with the rate for boys per 100.000 persons per year decreased from 1.9 in the first third of the study ...